Perizinan Jual Beli Minuman Beralkohol Tradisional di Indonesia Dalam Perspektif Peraturan Presiden Republik Indonesia Nomor 74 Tahun 2013 - Danilo Leonard Duan (International Forum of Researchers and Lecturers, 2025)
The circulation of alcoholic beverages is often unlicensed, particularly traditional alcoholic beverages, which are frequently distributed without a license due to being considered cultural heritage or customs specific to certain regions in Indonesia. This situation raises concerns regarding both legal compliance and public health. This research examines the licensing process for the sale and purchase of traditional alcoholic beverages in Indonesia, focusing on the Presidential Regulation of the Republic of Indonesia Number 74 of 2013 concerning the Control and Supervision of Alcoholic Beverages as an analytical framework. The study aims to explore the regulatory environment surrounding the distribution of these beverages and evaluate the challenges and opportunities for obtaining proper licenses. The research further discusses the role of the Online Single Submission Risk Based Approach (OSS-RBA) system, a digital platform designed to simplify the licensing process for businesses. This study is expected to serve as a valuable reference and knowledge resource for the public, providing clarity on the licensing process for alcoholic beverages. It also aims to raise awareness of the legal framework and facilitate smoother and more transparent processes for distributing alcoholic beverages in Indonesia.